2020
DOI: 10.3847/1538-4357/aba7bb
|View full text |Cite
|
Sign up to set email alerts
|

First Constraints on Compact Dark Matter from Fast Radio Burst Microstructure

Abstract: Despite existing constraints, it remains possible that up to 35% of all dark matter is comprised of compact objects, such as the black holes in the 10–100 M ⊙ range whose existence has been confirmed by LIGO. The strong gravitational lensing of transients such as fast radio bursts (FRBs) and gamma-ray bursts has been suggested as a more sensitive probe for compact dark matter than intensity fluctuations observed in microlensing experiments. Recently the Australian Square Kilometre Array Pathf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…FRBs can potentially be observably gravitationally lensed and probe dark matter distributions in the Universe (e.g., Muñoz et al 2016;Sammons et al 2020). Whether wave effects are directly visible in the burst morphology of an FRB depends on the Fresnel scale of the lensing scenario, which in turn depends on the physical parameters of the lens and the observing frequency.…”
Section: Implications For Frbs As Astrophysical Toolsmentioning
confidence: 99%
“…FRBs can potentially be observably gravitationally lensed and probe dark matter distributions in the Universe (e.g., Muñoz et al 2016;Sammons et al 2020). Whether wave effects are directly visible in the burst morphology of an FRB depends on the Fresnel scale of the lensing scenario, which in turn depends on the physical parameters of the lens and the observing frequency.…”
Section: Implications For Frbs As Astrophysical Toolsmentioning
confidence: 99%
“…FRBs have temporal profiles that range from tens of microseconds to several milliseconds, which is shorter than the anticipated delay (∼1 ms) caused by multi-path propagation due to the gravitational lensing of compact objects (e.g., 10-100 M blackholes) [194]. Extremely high time resolution studies of FRBs and detection of few-microsecond temporal structure such as for FRB 181112 [195] could potentially detect multiple burst copies generated as a consequence of lensing [194]. Methods to distinguish copies of a burst through a lensing event have been developed and applied to FRB data by Farah et al [71] and Cho et al [195], based on the expectation of spatial coherence of the emission, which will be manifested as correlation in the voltages between pulses.…”
Section: Hubble Parametermentioning
confidence: 84%
“…FRBs have temporal profiles that range from tens of microseconds to several milliseconds, which is shorter than the anticipated delay (∼1 ms) caused by multi-path propagation due to the gravitational lensing of compact objects (e.g., 10-100 M blackholes) [194]. Extremely high time resolution studies of FRBs and detection of few-microsecond temporal structure such as for FRB 181112 [195] could potentially detect multiple burst copies generated as a consequence of lensing [194].…”
Section: Hubble Parametermentioning
confidence: 96%
See 1 more Smart Citation
“…They concluded that f DM in MACHO is constrained to < 0.001 when there were no search of multiplepeaked FRBs for time intervals larger than 1 ms and flux ratio less than 10 3 . These methods of using FRBs to find dark matter in MACHO is widely studied later [261][262][263][264][265].…”
Section: Hubble Parameter H(z)mentioning
confidence: 99%